2018
DOI: 10.1093/jas/sky394
|View full text |Cite
|
Sign up to set email alerts
|

Relative bioavailability ofl-lysine sulfate is equivalent to that ofl-lysine HCl for nursery piglets1

Abstract: Supplementary l-lysine sources include l-lysine HCl and l-lysine sulfate. l-Lysine sulfate contains at least 50% l-Lys and other components as residues from the fermentation process, other amino acids, and other organic and inorganic substances, being an alternative to l-Lys HCl. The aim of this study was to evaluate the relative bioavailability (RBV) of l-Lys sulfate in comparison with l-Lys HCl and its effects on performance, blood parameters, intestinal functionality, and the apparent total tract digestibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…1A to F). In agreement with current results, Palencia et al (2019) and Htoo et al (2016) reported equivalent bioavailability between these two Lys sources using ADG and G:F as response criteria in nursery pigs (6 to 21 kg) and growing pigs (57 to 87 kg), respectively. The lack of difference in RBV between l-Lys sulfate and l-Lys HCl also agreed with the lack of differences in ADG, G:F, and digestibility of DM and S between the two Lys sources observed in this study.…”
Section: Resultssupporting
confidence: 91%
“…1A to F). In agreement with current results, Palencia et al (2019) and Htoo et al (2016) reported equivalent bioavailability between these two Lys sources using ADG and G:F as response criteria in nursery pigs (6 to 21 kg) and growing pigs (57 to 87 kg), respectively. The lack of difference in RBV between l-Lys sulfate and l-Lys HCl also agreed with the lack of differences in ADG, G:F, and digestibility of DM and S between the two Lys sources observed in this study.…”
Section: Resultssupporting
confidence: 91%
“…Lysine sulphate is a fermentation by‐product containing 50% of Lysine, other amino acids and organic and inorganic substances (Ahmad et al, 2007; Smiricky‐Tjardes et al, 2004). The addition of lysine sulphate to the diet of piglets has the same bioavailability and provides the same average daily gains and plasma urea as lysine hydrochloride (Palencia et al, 2019). A reduction in dietary lysine can promote the decomposition of protein, increasing the content of free glutamic acid, which improves the flavour of chicken breast meat (Watanabe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted that demonstrate an equal bioavailability of L-Lys HCL and L-Lys sulfate with biomass in nursery, growing, and finishing pigs ( Smiricky-Tjardes et al, 2004 ; Liu et al, 2007 ; Htoo et al, 2016 ; Li et al, 2019 ; Palencia et al, 2019 ). Similar results have been reported in pigs fed tryptophan and valine sources with biomass compared to pigs fed the same amino acid level using crystalline sources ( Oliveira et al, 2019 ; Wensley et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%